2016
DOI: 10.1136/gutjnl-2016-311508
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine acyltransferase 1 is downregulated by hepatitis C virus: impact on production of lipo-viro-particles

Abstract: We have identified LPCAT1 as a modulator of liver lipid metabolism downregulated by HCV, which appears as a viral strategy to increase the triacylglycerol content and hence infectivity of viral particles. Targeting this metabolic pathway may represent an attractive therapeutic approach to reduce both the viral titre and hepatic steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…Amounts of albumin secreted into the medium were determined by the human albumin ELISA Quantitation Kit (Bethyl; http://www.bethyl.com) following manufacturer’s instructions. Levels of APOB100 secreted into the medium were quantified by using the total human ApoB ELISA assay from ALerCHEK, as previously described [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amounts of albumin secreted into the medium were determined by the human albumin ELISA Quantitation Kit (Bethyl; http://www.bethyl.com) following manufacturer’s instructions. Levels of APOB100 secreted into the medium were quantified by using the total human ApoB ELISA assay from ALerCHEK, as previously described [24].…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were performed at day 3 post-inoculation except for the assessment of HCV genome replication, which was done at day 1 post-inoculation, i.e., under conditions of a single infection cycle. Indeed, at later time points, multiple rounds of infection are expected to cause a bias in the assessment of viral genome replication per se if the production of viral particles is affected [24].…”
Section: Methodsmentioning
confidence: 99%
“…Given the important roles of phospholipids in LDs and VLDL metabolism, it is conceivable that phospholipids may have roles in HCV infection. In a recent study, Beilstein et al (134) demonstrated that HCV infection in primary human hepatocytes and Huh7.5.1 cells inhibits gene expression of LPCAT1. LPCAT1 depletion increases the production of HCV particles with high infectivity, likely through remodeling LD metabolism and modulating VLDL secretion.…”
Section: Lpcat1 In Hepatitis C Virus Infectionmentioning
confidence: 99%
“…Recent studies favor the role of lipid mobilization from lipid droplets in the morphogenesis and secretion of HCV LVPs. The knockdown of the lipid droplet phospholipid-remodeling enzyme lysophosphatidylcholine acyltransferase 1 (LPCAT1) increases the cellular triacylglycerol content and HCV LVP secretion (24). Similarly, ␣/␤-hydrolase domain-containing 5 (ABHD5), a lipid droplet-associated lipase, is required for the assembly and release of HCV LVPs (25).…”
mentioning
confidence: 99%